Information Literacy Among Users of Selected Children's Library in Nigeria - Mesagan, Olanike Faith (South Sulawesi Education Development (SSED), 2024)
Information literacy among children in the contemporary world has bring about the need to investigate the importance of children libraries in acquiring literacy among library users. The study investigated information literacy skills for effective information resource utilization among users of Children Center Library, University of Nigeria Nsukka. The study used qualitative study design, data was collected using focus group discussion. Content analysis was use for data analysis. Instrument was validated by three (3) experts (two from Department of Library and Information and one from measurement and evaluation unit of the Department of Science Education), University of Nigeria, Nsukka. Findings revealed that children in CCL lacks the ability to recognize the needed information, to search and locate needed materials on catalogues. It also revealed that important skills are needed by the children. The extent of application of information literacy skills among the children is on the average. The barriers to information literacy among the users includes lack of access to information sources in the center library, limited parental involvement, information overload, peer pressure, spending much time on television, poor knowledge of librarians, fear of rejection among mates, language barriers, etc. Solutions include provision of unlimited access to information sources, parents assisting their kids at home, adequate training of librarians, good relationship between the children and staff, giving children sufficient time in the library and language tutoring among others.